Public Speaking Training for Youth in Koto Perambahan Village, Kampar Regency in Improving Public Speaking Skills - Syahputra, Dasa Syawal; Azwan Ali; M. Ikhsan Alfasiri; Herdiansyah Putra; Raja Muhammad Husein (ASSUNNAH PRESS, 2023)
The ability to speak in public (Public Speaking) for a teenager is one of the abilities that greatly supports activities in working and doing various creativity. Especially in the current era of technological advancement, there are many things that can be done by teenagers as an effort to make breakthrough changes in a positive direction by mastering Public Speaking. It's just that the fact that many teenagers do not have good public speaking skills to convey ideas in public so that it hampers their efforts in this regard. The purpose of this activity is to uncover potential as well as an effort to help Koto Perambahan Village teenagers in improving their skills in the field of Public Speaking or public speaking skills. Public speaking skills are something that must be trained from an early age; Because it will be beneficial for the future. The method of implementing service consists of preparation, implementation and evaluation. The result of this activity is that the trainee teenagers have demonstrated their Public Speaking skills after getting direction and guidance.